Fascia as a regulatory system in health and disease - Slater, Alison M.; Barclay, S. Jade; Granfar, Rouha M. S.; Pratt, Rebecca L. (Frontiers in Neurology, 2024)
Neurology and connective tissue are intimately interdependent systems and are critical in regulating many of the body’s systems. Unlocking their multifaceted relationship can transform clinical understanding of the mechanisms involved in multisystemic regulation and dysregulation. The fascial system is highly innervated and rich with blood vessels, lymphatics, and hormonal and neurotransmitter receptors. Given its ubiquity, fascia may serve as a “watchman,” receiving and processing information on whole body health. This paper reviews what constitutes fascia, why it is clinically important, and its contiguous and interdependent relationship with the nervous system. Unquestionably, fascial integrity is paramount to human locomotion, interaction with our environment, bodily sense, and general physical and emotional wellbeing, so an understanding of the fascial dysregulation that defines a range of pathological states, including hypermobility syndromes, autonomic dysregulation, mast cell activation, and acquired connective tissue disorders is critical in ensuring recognition, research, and appropriate management of these conditions, to the satisfaction of the patient as well as the treating practitioner.